PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. VISI CAKRAWALA PRATAMA - Rusdi Muklis Prasetyo; Burhan Stafrezar (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Human resources are pivotal in driving an organization towards its overarching objectives. The inherent rationality and intelligence possessed by individuals have a profound impact on guiding an organization, rendering them indispensable assets for leadership that significantly influence an organization's prosperity. This study is centered on the examination of PT. Visi Cakrawala Pratama. Within this organization, we seek to unravel how specific factors, such as corporate culture and management styles, exert their influence on employee well-being within the workplace, leveraging quantitative research methods and statistical analysis through tools like SPSS and multiple linear regression. This study encompasses 70 participants, representing the entire staff of PT. Visi Cakrawala Pratama, and their insights were collected through an online questionnaire. The results of this research unveil a substantial connection between organizational culture, leadership, and the primary metric of employee job satisfaction at PT. Visi Cakrawala Pratama. The implications of these findings extend to both researchers and practitioners, offering a solid theoretical framework for further exploration into the intricate relationship between organizational culture, leadership styles, and the contentment of employees. This study underscores the critical role that human resources and leadership play in shaping the trajectory of an organization's success.